2022
DOI: 10.1128/spectrum.02108-21
|View full text |Cite
|
Sign up to set email alerts
|

The PqsE-RhlR Interaction Regulates RhlR DNA Binding to Control Virulence Factor Production in Pseudomonas aeruginosa

Abstract: Bacteria use a cell-cell communication process called quorum sensing (QS) to orchestrate collective behaviors. QS relies on the group-wide detection of molecules called autoinducers (AI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(118 citation statements)
references
References 47 publications
13
89
1
Order By: Relevance
“…Deletion of the gene encoding the enzyme, PqsE, that acts in a different P. aeruginosa QS pathway, results in the identical loss of pathogenic phenotypes as occur following deletion of rhlR (8). Consistent with this result, we recently showed that PqsE and RhlR make a protein-protein interaction that enhances the affinity of RhlR for target DNA sequences (9, 10). The PqsE-RhlR interaction is, moreover, essential for RhlR-controlled QS phenotypes.…”
Section: Observationsupporting
confidence: 71%
“…Deletion of the gene encoding the enzyme, PqsE, that acts in a different P. aeruginosa QS pathway, results in the identical loss of pathogenic phenotypes as occur following deletion of rhlR (8). Consistent with this result, we recently showed that PqsE and RhlR make a protein-protein interaction that enhances the affinity of RhlR for target DNA sequences (9, 10). The PqsE-RhlR interaction is, moreover, essential for RhlR-controlled QS phenotypes.…”
Section: Observationsupporting
confidence: 71%
“…Our finding that the PqsE-RhlR interaction was disrupted following introduction of the E182W substitution in the PqsE active site was surprising given that this residue is distal to the RhlR interaction site (21). The crystal structure of PqsE(E182W) revealed that a loop rearrangement inserts the E280 residue into the active site to coordinate both of the iron atoms at this site.…”
Section: Discussionmentioning
confidence: 91%
“…6xHis-PqsE proteins were purified for biochemical assays (tagged) and crystallography (tag removed) as described previously (20). Enzyme activities of purified 6xHis-PqsE variants were measured as previously reported with 4-methylumbelliferyl butyrate (MU-butyrate) as the substrate (21). Fluorescence polarization assays with the BB562 active site probe were performed as described (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the LasI/LasR and RhlI/RhlR QS systems, the 2-heptyl-3-hydroxy-4(1H)-quinolone ( Pseudomonas quinolone signal, PQS) circuit is the third system regulated by PqsR, which relies on PQS. Recently, many studies reported the interaction between Rhl and Pqs systems [ 9 , 10 , 11 ]. RhlR negatively regulates the expression of pqsABCDE operon independently of PQS production.…”
Section: Introductionmentioning
confidence: 99%